Reviewing some water resources management strategies (Globally, Arabic, local) - Essa Yass, Bahaa; Ali Mhaibes, Hussam (Journal of Economics and Administrative Sciences, 2024)
The issue of water has taken a large place in the writings of researchers and decision-makers at global, Arab, and local levels, especially in arid and semi-arid regions for many reasons. Water resources, especially those shared by more than one country, are also a source of conflict and tension between countries and will constitute the arena of future conflict under the name of (water war). There are many international studies concerned with the strategic management of water resources, and each study took a specific aspect according to the priority that researchers see in diagnosing the problem, which confirms the existence of a water crisis at the global level. Researchers have differed in presenting strategies for managing water resources, some of them gave priority to the stakeholders in solving the problem, while others focused on environmental analysis, still, some indicated the importance of strict internal management, and others found that the legal and political axis is the most important in strategies. In Iraq, the water problem is complex. It consists of all the previous axes, and this requires formulating a strategy based on an accurate analysis of these factors to come up with a strategic choice commensurate with the size of these challenges to address this serious crisis. Therefore, our choice of international, Arab, and local studies similar to the case of Iraq will contribute to clarifying the proposed strategy to shorten the effort and time; this is done by analysing the strategies in question to benefit from them in drawing the features of Iraqi strategy. Research type: Literature review